2007
DOI: 10.1007/s00405-007-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

Residual hearing in cochlear implant patients

Abstract: Preservation of residual hearing should be a desirable outcome of implant surgery. Prevention of neural degeneration due to loss of residual hair cells, together with the continuous progress in cochlear implant technology should be able to preserve cochlear integrity as well as possible. The degree of hearing preservation may vary depending on surgical approach, maximum insertion depth and other factors not uniformly considered to date. The aim of this retrospective case controlled study is to evaluate residua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 13 publications
3
37
0
1
Order By: Relevance
“…The maximal output of the Grason-Stadler GS61audiometer (Grason-Stadler™, Minnesota, USA; calibrated in line with American National Standards Institute standards) was 120 dB HL for frequencies 250 to 4000 Hz, and 110 dB HL for 8000 Hz. A value of 5 dB was added to the maximal output threshold of the testing frequency where no responses could be found above the limit [8], [9], [10]. Elapsed time after operation for the postoperative PTA exam was about 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…The maximal output of the Grason-Stadler GS61audiometer (Grason-Stadler™, Minnesota, USA; calibrated in line with American National Standards Institute standards) was 120 dB HL for frequencies 250 to 4000 Hz, and 110 dB HL for 8000 Hz. A value of 5 dB was added to the maximal output threshold of the testing frequency where no responses could be found above the limit [8], [9], [10]. Elapsed time after operation for the postoperative PTA exam was about 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…The maximal output of the Grason-Stadler GS61audiometer (Grason-StadlerÔ, Eden Prairie, MN, USA; calibrated in line with American National Standards Institute standards) was 120 dB HL for frequencies 250-8000 Hz. A value of 5 dB was added to the maximal output threshold of the testing frequency where no responses could be found above the limit [9][10][11]. The time elapsed after operation for the postoperative PTA and CI levels examination of all patients was about 1 month.…”
Section: Audiometric Examinationmentioning
confidence: 99%
“…HP is generally defined by an allowable change of HTL (preoperatively versus postoperatively) that may be 10 dB HL (7,13,15,17,18), 20 dB (5,7), 30 dB (3,13), or 40 dB (18). Some have defined HP as the preservation of any measurable hearing (2,5,8,9,12,13,15,17). The frequencies used to determine HP may vary between studies and have not always been precisely reported (2,7,17).…”
Section: Discussionmentioning
confidence: 97%